Genetic score of power-speed and endurance track and field athletes - Ben-Zaken, S.; Meckel, Y.; Nemet, D.; Eliakim, A. (Scandinavian Journal of Medicine & Science in Sports, 2015)
Athletic excelling capability in a specific sport results from the combined influence of hundreds of genetic polymorphisms. The aim of the current study was to characterize athletes' polygenetic scores. We developed two polygenetic scores: (a) Power Genetic Distance Score based on two polymorphisms (PGDS2; ACEI/D, ACTN3C/T) or five polymorphisms (PGDS5; ACTN3C/T, ACEI/D, IL6-174G/C, NOS3T/C, AGTMET235THR); and (b) Endurance Genetic Distance Score based on two polymorphisms (EGDS2; ACEI/D, ACTN3C/T) or five polymorphisms (EGDS5; PPARGC1AGly482Ser, PPARAintron7G/C, PPARDT294C, NRF2A/C, HIFC/T). Eighty-two power-speed athletes, 87 endurance athletes, and 119 nonathletic controls participated in the study. Genomic DNA was extracted from peripheral blood. Power-speed athletes' mean PGDS2 (46.1) and PGDS5 (29.4) were significantly higher compared with their mean EGDS2 (36.4) and EGDS5 (23.1; P < 0.05, P < 0.01, respectively); and compared with controls' mean PGDS2 (36.6) and PGDS5 (24.2; P < 0.05, P < 0.05, respectively). Endurance athletes' mean EGDS2 (60.3) and EGDS5 (35.3) were significantly higher compared with their mean PGDS2 (26.9) and PGDS5 (21.8; P < 0.001, P < 0.001, respectively); and compared with controls' mean EGDS2 (51.2) and EGDS5 (26.1; P < 0.05, P < 0.001, respectively). We conclude that polygenetic scores can differentiate power-speed from endurance athletes. Whether these scores may be used to identify elite power-speed or endurance athletes' needs to be addressed in future studies.